DEEP STRUCTURE OF THE TURKESTAN PALEOOCEAN SUTURE: (NORTHEASTERN FERGANA) - Lesik O.M.; Mikolaichuk A.V. (My University, 2001)
The types and subtypes of a density section of the Earth's crust in the zone limited by the Talas-Fergana and East Fergana faults are considered. The zone has an deconsolidated inversion layer in the lower crust (35-50 km). Rock densities are calculated by an empirical formula with the use of seismic tomography data on P-and S-wave velocities. In the geological aspect this territory is remarkable as it involves the South Tien Shan ophiolite belt notching a suture which resulted from the closure of Turkestan paleoocean in the Middle Carboniferous. In the Earth's crust section the suture is traceable to a depth of 15-20 km, is cone-shaped, and is characterized by an increased density of rocks. Analysis of the gravimetric field and density sections suggests that within this cone the Earth's crust is saturated with rocks of ophiolite association.
Keywords: Inversion layers; density of rocks; Turkestan paleo-ocean; suture